DIRECT EFFECTS OF THE CAP IMPLEMENTATION IN POLAND - EXPECTATIONS UP TO 2020 - Wigier, Marek; Darvasi, Doina (Economics of Agriculture, 2012)
When Poland accessed the EU it was covered by regulations signifcantly changing the conditions of food economy. Mutual opening of markets multiplied the possibilities of market outlets and contributed to the better competitiveness of economic entities. The launched public funds helped, for instance, to modernise farms and food industry businesses, improvement of their competitiveness, construction of infrastructure or multifunctional development of rural areas. This paper discusses the selected effects of the CAP implementation in Poland at the background of production and economic situation in the agri-food sector and the most important challenges.